Religious Impact on Media Co-regulation: a Case Study of Russia - Khroul, Victor (Žurnalistikos tyrimai, 2015)
The proposed paper is focused on media co-regulation and civic accountability from the perspective of religious ethos. The author analyses the process of religion mediatization in the Russian public sphere and presents the findings of a case study of the project entitled “Public Council on Morality for TV”. Classifying different situations when religions face the media and vice versa, the paper presents some empirically fixed facts and trends of dysfunction and corruption in the religious life coverage in Russia. Drawing attention to several particular features of the Russian context (public opinion, autonomy of journalists, agenda-setting and management problem, etc.), the author puts forward a set of significant obstacles for the moral control of the media: the axiological problem (the lack of value consensus in the Russian society), the evaluative problem (absence of a moral monitoring in the mass media and the public sphere), and the communicative problem (the absence of a well-articulated dialogue of value systems).